1982
DOI: 10.1007/bf02381446
|View full text |Cite
|
Sign up to set email alerts
|

Birth Intervals inM. sylvanus of Gibraltar

Abstract: ABSTRACT. The length of the birth interval in Macaea sylvanus of Gibraltar was defined and oneyear intervals were found to be normative. The effect of infant loss on the interbirth interval was assessed and found to have no influence.Variability in the birth interval in comparable species is noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
2
9
0
1
Order By: Relevance
“…In fact, the above authors reported that females which lost their own infants within 6 months of life, and hence were not lactating during the mating season, had shortened interbirth intervals (1 year). Data from other species of macaques are also consistent with the hypothesis that the pres ence of an infant affects the female's repro ductive cyclicity [Koford, 1965;Vandenbergh and Vessey, 1968;Drickamer, 1974;Angst, 1978;Hadidian and Bernstein, 1979; but see Burton and Sawchuk, 1982], Thus, in Macaca spp., evidence exists in support of a view that lactation is a mechanism that plays a central role in controlling reproduction [Short, 1976], The present study shows that the inter birth intervals experienced by the Rome group of Japanese macaques were shortened (1 year) and were not consistently affected by stillbirth and infant loss within 6 months of life. These results suggest that lactation was ineffective in restraining fertility in the study group.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, the above authors reported that females which lost their own infants within 6 months of life, and hence were not lactating during the mating season, had shortened interbirth intervals (1 year). Data from other species of macaques are also consistent with the hypothesis that the pres ence of an infant affects the female's repro ductive cyclicity [Koford, 1965;Vandenbergh and Vessey, 1968;Drickamer, 1974;Angst, 1978;Hadidian and Bernstein, 1979; but see Burton and Sawchuk, 1982], Thus, in Macaca spp., evidence exists in support of a view that lactation is a mechanism that plays a central role in controlling reproduction [Short, 1976], The present study shows that the inter birth intervals experienced by the Rome group of Japanese macaques were shortened (1 year) and were not consistently affected by stillbirth and infant loss within 6 months of life. These results suggest that lactation was ineffective in restraining fertility in the study group.…”
Section: Discussionsupporting
confidence: 68%
“…139], Especially in primiparous and old multiparous females birth intervals are pro longed. These results correspond to findings for M. sylvanus in Gibraltar [Burton and Sawchuk, 1982], Macaca mulatto [Missakian-Quinn andVarley, 1977, cited in Mit chell, 1979], Macaca arctoides [Silk et al, 1981], Macacafascicularis [Thommen, in preparation] and M.fuscata [Hiraiwa, 1981], A strategy of prolonged 'maternal invest ment' in the last-born infant is also practised by mothers who lost their previous infant, or who did not bear an infant in the preceding year. Here, too, a prolongation of the birth interval could be discerned [Thommen, in preparation].…”
Section: Discussionsupporting
confidence: 65%
“…A time span of 1 year between births can be considered as the norm [Burton and Sawchuk, 1982], In contrast to findings from other species [Tanaka et al, 1970;Asanov, 1972;Nomura et al, 1972;Angst and Thornmen, 1977;Angst, 1978;Hadidian and Bern stein, 1979] infant loss does not shorten the birth interval [Burton and Sawchuk, 1982], Concerning this matter Altmann et al [1978] state that 'Infant loss will have a greater impact on shortening interbirth-intervals in species with year-round breeding than in those with discrete breeding seasons' (p. 1029). In seasonally breeding species, how ever, with a normal birth interval of 2 years, infant loss considerably affects the length of the birth interval [Macaca fuscata : Tanaka et al, 1970;Nomura et al, 1972].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toutefois, cette reprise pré coce des cycles, observée notamment en Akfadou en 1983, n'induit pas une réduction de l'intervalle entre les naissances, phénomène confirmé sur des populations semi-libres [Burton et Sawchuk, 1982;Paul et Thommen, 1984], Par contre, Paul et Thommen montrent que la non-fécondité d'une femelle induit une fertilisation et une parturition plus précoce l'année suivante [cf. aussi Koford, 1965;Drickamer, 1974, sur M. mulatto]-, on peut alors s'attendre à ce que les femelles de la troupe du Tigounatine mettent bas plus tôt en 1985.…”
Section: Discussion Et Comparaisonunclassified